Resposta de cultivares de soja a programas de controle de doenças - Gai, Rafael Pegoraro (2013)
Soybean development is affected by several factors. Fungal diseases are responsible for significant reductions on yield. In order to avoid these losses, fungicides must be used to control most of soybean diseases. The need of a profitable crop all strategies that reduce the negative impact on yield are being developed. The objective of this study was to determine the response of soybean varieties to disease control programs in different sowing dates. An experiment was carried out at the experimental station of Phytus Institute, Itaara/RS, in the central region of Rio Grande do Sul during 2011/2012 season. The experimental design was a randomized block design with four replications in a factorial design with split plots (2x2x10). The experimental factors were two sowing dates, two varieties and ten control programs. The results indicated that three applications of mixtures prothioconazole + trifloxystrobin and azoxystrobin + ciproconazol controlled rust and powdery mildew of soybeans regardless of sowing date and cultivar. The use of protective programs increased yield. The data show that the sowing date has directly related to the productivity.